Implicit motives - Schultheiss, Oliver C., 1967-; Brunstein, Joachim C. (New York ; Oxford : Oxford University Press, 2010)
How do unconscious motivational needs influence physiological cognitive, affective, and behavioural responses to incentives? How can implicit motives be measured? These are some of the topics this book presents in 18 chapters, contributed by leading authorities in the field.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Motivation (Psychology)